Efforts to achieving SDGs in Durian Village through increasing community participation - Arafik Lamadi; Miftahul Khair Kadim (Fisheries and Society, 2022)
Students community service activities are a form of UNG in supporting government development programs for the realization of SDGs in the villages of Gorontalo Province. One of the villages where KKNT activities are located is Durian Village. This activity was carried out for 50 days in September-November 2021 involving 30 students and 2 lecturers as field assistants. The purpose of implementing this KKN build village program was to encourage and help the community to contribute to the development and foster a responsive attitude of the village government to the potential opportunities and problems in the village. This activity was succeeded in increasing the awareness of the people and olso succeeded in facilitating village government achieve the Village SDGs.